10-Year Results of Standard Cross-Linking in Patients with Progressive Keratoconus in Romania. (7th March 2019) - Nicula, Cristina; Pop, Radu; Rednik, Anca; Nicula, Dorin
Abstract : Purpose . The purpose of the current study was to evaluate the long-term functional results based on keratometric measurements, spherical and cylinder equivalent in patients with progressive keratoconus treated with conventional "epi-off" corneal collagen cross-linking (CXL). Methods . We conducted a retrospective study in which 113 eyes from 90 keratoconus-treated patients with CXL between 2006 and 2008 in Oculens Eye Clinic from Cluj-Napoca, Romania, were included. The diagnosis of keratoconus was based on corneal topography and its clinical signs. All patients were evaluated preoperatively, and a follow-up was performed at 1, 3, and 6 months and every year from 1 to 10 years after conventional CXL. Results . All keratometry measurements improved significantly during the follow-up. Compared to preoperative values, the improvement of K max become statistically significant at 1 year after CXL (mean change compared to baseline −0.9 D, p < 0.001 ) and remained statistically significant thereafter up to 10 years (mean change compared to baseline −2.3 D, p < 0.001 ). As compared to preoperative values, mean spherical equivalent and mean cylinder improved during the follow-up, from a mean of −6.22 D before CXL to a mean value of −5.0 at 10 years, following CXL for spherical equivalent and from −4.4 D at baseline to −3.4 D at 10 years for cylinder (p < 0.05 for both). Uncorrected visual acuity increased, remaining statistically significant, by 0.104 logMAR at 10 years after CXL (p = 0.0015 ), and best-corrected visual acuity increased by 0.135 logMAR at 10 years after CXL (p = 0.015 ). We did not observe any case of severe complication. Conclusion . Our results show that CXL has a favorable effect on the progression of KC. The reduced K values, cylinder and spherical equivalent, and increased visual acuity remained the same 10 years after the procedure.